(3ZGjGJ GdCacGQ hfgGjGJ GdCacGQ GdeMjWI HYLGFH GdHMQ GdRNGQs - (3CMeO Hf jMji Hf GdeQJVi GdegOi dOjf Gddgs; (3CMeO Hf jMji Hf GdeQJVj GdRjOj,J (B840 (3g` s ((3eMeO Hf GdYjOQhS s)
(3ChdgG (B:s
(3Gddge Ef Cgd GdKfGA jbUQ Yf hUa LdGdc gPG hdeG ef Gddg HceGd eG CQOfGg ef JCdja cJGH dWja jJVef GdEMGWI HYdhe GdESdGe LejYgG , CUhdgG haQhYgG s
(3BNQgG (B:s
(3hEPG UOQJ ef HYV Cgd GdHjJ ZSJMb YdjgG KeGfjf LRAkG ef GdKhGH , abO UGQ GdKhGHGf hEf JaGVdG hHJeGe gPg GdLedI Je cJGH GdefjI hGdCed hjJdhg cJGH GdOQQ Je s
(3GdLRA GdChd hSeGg GdeDda GdefjI hGdCed TQM Gdedd hGdfMds
(3GdfSNI HgG MhGTs
(3fSNI ebGHdI Ydi GdfSN GdCe GdJi fbdJ efgG aEf cGfJ gPg GdCNjQI ZjQ ebGHdI hJeJ GdebGdI ai (B1073(3g`s
(3cJHJ HQSe GdbGVi LeGd GdOjf SYjO Hf fGUQ GdTGhQi hYdjgG Jedc HESeg s
(3HgG fXGe GdJYbjHI s
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdESdGejs